2009
DOI: 10.1021/jf803148z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Stoichiometry of the Reaction of Chlorogenic Acid and Its Alkyl Esters against the DPPH Radical

Abstract: The lipophilization of polar antioxidants such as phenolics is an efficient way to enhance their solubility in apolar media. Thus, in emulsified systems, lipophilized antioxidants are supposed to locate at the lipid/aqueous phase interface and to lead to a better protection of unsaturated lipids. Herein, the antiradical activity of chlorogenic acid (5-CQA) and its corresponding esters with seven fatty alcohols (from methanol to eicosanol) have been achieved using the well-known 2,2-diphenyl-1-picrylhydrazyl (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 27 publications
(68 reference statements)
4
28
0
1
Order By: Relevance
“…This step is typically followed by a much slower decrease in visible absorbance, featuring the residual H-donating ability of the antioxidant degradation products (slow step). It is worth mentioning here that only the fast stages of the reaction (100 s) were detailed in terms of kinetic analysis (Scheme 2), where it is commonly accepted that the stabilization of DPPH radicals results from the transfer of the most labile H atoms of the antioxidants (-OHs) [29]. The rate constant (k) of the reaction was determined in all the systems at 25 • C by monitoring the decay of DPPH absorbance at 515 nm.…”
Section: Evaluation Of Dpph Scavenging Activity Of Rutinmentioning
confidence: 99%
See 1 more Smart Citation
“…This step is typically followed by a much slower decrease in visible absorbance, featuring the residual H-donating ability of the antioxidant degradation products (slow step). It is worth mentioning here that only the fast stages of the reaction (100 s) were detailed in terms of kinetic analysis (Scheme 2), where it is commonly accepted that the stabilization of DPPH radicals results from the transfer of the most labile H atoms of the antioxidants (-OHs) [29]. The rate constant (k) of the reaction was determined in all the systems at 25 • C by monitoring the decay of DPPH absorbance at 515 nm.…”
Section: Evaluation Of Dpph Scavenging Activity Of Rutinmentioning
confidence: 99%
“…The rate constant (k) of the reaction was determined in all the systems at 25 • C by monitoring the decay of DPPH absorbance at 515 nm. The rate of DPPH reduction under these conditions can be written as follows [26,29]:…”
Section: Evaluation Of Dpph Scavenging Activity Of Rutinmentioning
confidence: 99%
“…Recently, we have shown that chlorogenic acid (5‐caffeoylquinic acid, Figure 1), exhibiting antioxidant [10] and antiradical [11] properties in test tube‐based assays, can be lipophilized by various fatty alcohols in a two‐step lipase‐catalysed transesterification strategy [12] . This reaction leads to a homologous series of alkyl chlorogenate esters (from methyl to hexadecyl, Figure 1), which constitutes an interesting phenolic model to study the impact of the hydrophobicity on the antioxidant capacity in biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…This antioxidant activity is attributed to the presence of the ferulate group in its chemical structure. It should be considered that the presence of different groups esterified in a phenolic antioxidant may play an attenuating role or antioxidant capacity enhancement (López, Laguerre, Lecomte, Figueroa, Barea, Weiss, Decker, & Villeneuve, 2009). Therefore, it is important to study and compare its antioxidant power with that of other antioxidants in different types of oils.…”
Section: Introductionmentioning
confidence: 99%